A new sinistral species of the land-snail genus Satsuma (Pulmonata: Camaenidae) from China. (2nd January 2020) - Zhang, Le-Jia; Zhu, Yi-Jie; Lyu, Zhi-Tong
ABSTRACT: The species of Satsuma are mostly endemic to East Asia except for one species distributed in Batan Island of the Philippines. More than 99% of the known species of this genus are endemic to the island environment. Only three species are currently known to occur on the mainland. Here we describe a new sinistral Satsuma species from China, Satsuma guandi n. sp. We studied the shell morphology and genital anatomy of the new species and reconstructed the molecular phylogeny of the genus based on partial nucleotide sequences of the mitochondrial gene cytochrome c oxidase subunit I and nuclear markers from the ribosomal RNA cistrons (the internal transcribed spacer and the external transcribed spacer regions). The new species differs from other sinistral Satsuma species by having a strongly angulated shell and an open dark brownish-red umbilicus. The new species also differed from all other sinistral congeners in details of its reproductive anatomy. The molecular analysis supports the validity of the new species within the genus Satsuma .